Shielding of a Lipooligosaccharide IgM Epitope Allows Evasion of Neutrophil-Mediated Killing of an Invasive Strain of Nontypeable Haemophilus influenzae - Jeroen D. Langereis (American Society for Microbiology, 2014)
ABSTRACT Nontypeable Haemophilus influenzae is a frequent cause of noninvasive mucosal inflammatory diseases but may also cause invasive diseases, such as sepsis and meningitis, especially in children and the elderly. Infection by nontypeable Haemophilus influenzae is characterized by recruitment of neutrophilic granulocytes. Despite the presence of a large number of neutrophils, infections with nontypeable Haemophilus influenzae are often not cleared effectively by the antimicrobial activity of these immune cells. Herein, we examined how nontypeable Haemophilus influenzae evades neutrophil-mediated killing. Transposon sequencing (Tn-seq) was used on an isolate resistant to neutrophil-mediated killing to identify genes required for its survival in the presence of human neutrophils and serum, which provided a source of complement and antibodies. Results show that nontypeable Haemophilus influenzae prevents complement-dependent neutrophil-mediated killing by expression of surface galactose-containing oligosaccharide structures. These outer-core structures block recognition of an inner-core lipooligosaccharide epitope containing glucose attached to heptose HepIII-β1,2-Glc by replacement with galactose attached to HepIII or through shielding HepIII-β1,2-Glc by phase-variable attachment of oligosaccharide chain extensions. When the HepIII-β1,2-Glc-containing epitope is expressed and exposed, nontypeable Haemophilus influenzae is opsonized by naturally acquired IgM generally present in human serum and subsequently phagocytosed and killed by human neutrophils. Clinical nontypeable Haemophilus influenzae isolates containing galactose attached to HepIII that are not recognized by this IgM are more often found to cause invasive infections. IMPORTANCE Neutrophils are white blood cells that specialize in killing pathogens and are recruited to sites of inflammation. However, despite the presence of large numbers of neutrophils in the middle ear cavity and lungs of patients with otitis media or chronic obstructive pulmonary disease, respectively, the bacterium nontypeable Haemophilus influenzae is often not effectively cleared from these locations by these immune cells. In order to understand how nontypeable Haemophilus influenzae is able to cause inflammatory diseases in the presence of neutrophils, we determined the mechanism that underlies resistance to neutrophil-mediated killing. We have shown that nontypeable Haemophilus influenzae prevents binding of antibodies of the IgM subtype through changes in their surface lipooligosaccharide structure, thereby preventing complement activation and clearance by human neutrophils.